2017
DOI: 10.1115/1.4036716
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Electrically-Assisted Manufacturing With Emphasis on Modeling and Understanding of the Electroplastic Effect

Abstract: Increasingly strict fuel efficiency standards have driven the aerospace and automotive industries to improve the fuel economy of their fleets. A key method for feasibly improving the fuel economy is by decreasing the weight, which requires the introduction of materials with high strength to weight ratios into airplane and vehicle designs. Many of these materials are not as formable or machinable as conventional low carbon steels, making production difficult when using traditional forming and machining strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 117 publications
0
33
0
1
Order By: Relevance
“…When the ratio of sheet thickness to grain size was small, the formability decreased [11]. The studies show that the current can reduce the flow stress, improve plasticity, and formability, this is called the electroplastic effect [12]. Ross et al [13] presented the direct current (DC) EA compression experiments of Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 99%
“…When the ratio of sheet thickness to grain size was small, the formability decreased [11]. The studies show that the current can reduce the flow stress, improve plasticity, and formability, this is called the electroplastic effect [12]. Ross et al [13] presented the direct current (DC) EA compression experiments of Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Breda et al [12] observed an Influence of stacking fault energy(SFE) in electrically assisted uniaxial tension. Ruszkiewicz et al [13] proposed the constitutive equation of the continuum theory of sintering to include the electric current effect term. However, a few other studies considered electro-plastic effect as a thermally dominated effect.…”
mentioning
confidence: 99%
“…It has been shown that in steady-state circumstances, the electroplastic effect can be fully modeled and predicted using a conventional energy balance and thermal softening approach that assumes 100% bulk (homogeneous) Joule heating [9,10]. These works use electricity to heat a part but allow the temperature to stabilize before starting deformation.The steady-state modeling approach implemented into a finite element analysis (FEA) cannot predict the transient stress drop caused by pulsed electric current even though the correct temperature profile is predicted [11][12][13].Experimental results comparing the flow stress results of specimen heated in a furnace to the same temperatures seen through electrically assisted deformation found that electrically assisted deformation had a lower stress than thermally assisted, suggesting bulk Joule heating cannot fully explain the transient electroplastic effect [7,[14][15][16][17][18]. Theories have been developed to explain the transient nature of the electroplastic effect; these include (a detailed review of electroplastic theories and models can be found in Ref.…”
mentioning
confidence: 99%